Transfer kulturowy a repertuar popularny: przypadek londyńsko-warszawski - Agata Łuksza (Pamiętnik Teatralny, 2018)
In the second half of the 19th century, Polish newspapers paid attention to British culture, history, and politics; and since Helena Modrzejewska joined the Warszawskie Theatres, Shakespearean drama featured prominently in the repertories of the Warsaw stage. Yet whereas the significance of Shakespeare’s work for the Polish (and Warsaw) theatre and culture of the 19th century has been appreciated and thoroughly investigated (just as the influence of English romantic poets on Polish literature), so far no one has looked into the potential inspiration with British, and especially London, popular repertories in the Polish theatre of the period. The article brings a review of Warsaw repertories since 1814/15 until 1900/01 with respect to this problem, focusing not only the Narodowy Theatre, transformed later into the Warszawskie Theatres, but also taking into account the offer of garden theatres, which dramatically changed the Warsaw theatre scene after 1868. The author’s statistics based on the repertories collected by the Polish Academy of Sciences and the Jagiellonian collection of information about foreign drama in Poland as well as press publications from the period are an integral part of the study presented in this article. The analysis of repertories, press publications, and travel diaries and memoirs reveals that despite the Polish fascination with the British Empire, its institutions, and civilisation, Polish theatre artists, including garden theatre entrepreneurs, consistently refused to stage plays of British popular theatre, which they viewed as barbaric and of poor taste. The nearly complete lack of cultural transfer between the London and Warsaw popular theatres, and the few exceptions discussed in this article, constitutes an enigma that cannot be fully explained by the geopolitical situation of Warsaw in the 19th century.